2022
DOI: 10.7150/jca.64747
|View full text |Cite
|
Sign up to set email alerts
|

CDCA8 Contributes to the Development and Progression of Thyroid Cancer through Regulating CDK1

Abstract: Background: This study aims to reveal regulatory role of cell division cycle associated 8 (CDCA8) in thyroid cancer progression and metastasis. Methods: A series of experiments in vivo and in vitro were performed to explore the function of CDCA8 in thyroid cancer. Results: Immunohistochemical analysis showed that CDCA8 expression levels were upregulated in thyroid cancer tissues compared with normal tissues, and were statistically correlated with tumor stage. Results of in vitro loss-of-function assay showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Previous studies have documented the functional relevance of CDCA8 in tumor cell apoptosis [ 21 , 22 ]. And first, to confirm the knockdown and overexpression efficiency, the qRT-PCR and Western blot analyses (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have documented the functional relevance of CDCA8 in tumor cell apoptosis [ 21 , 22 ]. And first, to confirm the knockdown and overexpression efficiency, the qRT-PCR and Western blot analyses (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [21,22], CDCA8 has been shown to be strongly associated with apoptosis in cancer cells. However, in our study, it was surprising that under normal cell culture conditions, the effect of CDCA8 expression status on Bca cells viability was negligible (Fig.…”
Section: Cdca8 Promotes Bca Cell Survival In Oxygen-deprived Environmentmentioning
confidence: 87%
“…CDCA8 stands as a pivotal regulatory gene in mitosis [27], exerting a crucial influence in various cancers by promoting cell proliferation and invasion, potentially functioning as an oncogene [28,29]. Earlier research has documented heightened transcriptional activity of CDCA8 in embryos, embryonic stem cells, and cancer cells [30,31]. However, a thorough pan-cancer investigation into the status of CDCA8 has not been undertaken until now.…”
Section: Discussionmentioning
confidence: 99%